Double lung transplantation in patients with lung atelectasis and complete mediastinal shift. Issue 3 (1st March 2022) - Neto, Daniel M.; Chan, Ernest G.; Sanchez, Pablo G.
Abstract: Mediastinal shift and chest wall retraction limit the indication of a double lung transplant in patients with complete destruction of lung parenchyma. We report outcomes as well as preoperative and operative management in two patients with significant lung volume reduction and mediastinal shift due to bronchiectasis of the right lung. Abstract : For patients with complete atelectasis of one lung and severe mediastinal shift, double lung transplant without the need for lung reduction is a feasible option providing these patients with the maximum benefit of lung volumes after transplant.